Spousal Bereavement and Long-Term Care Needs of Older Chinese Adults - Peng Nie; Bin Zhang; Lanlin Ding; Alfonso Sousa-Poza (Institute of Labor Economics (IZA), 2025)
Leveraging nationally representative data from the 2011-2018 Chinese Longitudinal Healthy Longevity Study (CLHLS), this study examines the impact of spousal death on long-term care (LTC) needs among Chinese older adults aged 60 and above. Our results show that spousal bereavement significantly increases the probability of LTC needs by 5.0-9.1 percentage points across severity levels (low, medium, and high). Such adverse effects are much stronger among older individuals aged 75+. Our mechanism analysis identifies three key pathways through which spousal bereavement increases LTC needs, including the loss of primary caregiving, worsened emotional stress, and increased healthcare utilization especially for inpatient costs. Our findings highlight the urgent need for targeted LTC policies that support vulnerable widowed populations, particularly older widows.
Keywords: J12; J14; H55; I12; 330; emotional stress; primary caregiving; long-term care needs; spousal bereavement; healthcare utilization